2020
DOI: 10.1111/tan.13956
|View full text |Cite
|
Sign up to set email alerts
|

Binding affinities of 438 HLA proteins to complete proteomes of seven pandemic viruses and distributions of strongest and weakest HLA peptide binders in populations worldwide

Abstract: Funding information Australian Government Research Training Program Stipend (RTPS); AustralianWe report detailed peptide-binding affinities between 438 HLA Class I and Class II proteins and complete proteomes of seven pandemic human viruses, including coronaviruses, influenza viruses and HIV-1. We contrast these affinities with HLA allele frequencies across hundreds of human populations worldwide. Statistical modelling shows that peptide-binding affinities classified into four distinct categories depend on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
147
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(155 citation statements)
references
References 71 publications
7
147
0
1
Order By: Relevance
“…Very recent works employed different bioinformatic approaches to predict the best SARS-CoV-2 derived B and T cell epitopes and their associated HLA alleles, that may help to design effective vaccines and find protective antibodies [30][31][32][33][34][35]. Employing HLA binding affinity prediction tools, it has been observed that HLA-A and HLA-C alleles exhibited the relatively most and least capacity to present SARS-CoV-2 antigens, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent works employed different bioinformatic approaches to predict the best SARS-CoV-2 derived B and T cell epitopes and their associated HLA alleles, that may help to design effective vaccines and find protective antibodies [30][31][32][33][34][35]. Employing HLA binding affinity prediction tools, it has been observed that HLA-A and HLA-C alleles exhibited the relatively most and least capacity to present SARS-CoV-2 antigens, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent works employed different bioinformatic approaches to predict the best SARS-CoV-2 derived B and T cell epitopes and their associated HLA alleles, that may help to design effective vaccines and nd protective antibodies [21,[27][28][29][30][31]. Employing HLA binding a nity prediction tools, it has been observed that HLA-A and HLA-C alleles exhibited the relatively most and least capacity to present SARS-CoV-2 antigens, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing researches are trying to elucidate the mechanisms potentially responsible for inducing the immune response against SARS‐Cov‐2, including the role of HLA alleles in the affected individuals 4 . The HLA complex constitutes a specific group of molecules expressed on the cell surface, crucial for the recognition of nonself molecules by the acquired immune system.…”
Section: Healthy Italian Individuals (2034 Haplotypes) Covid‐19 Italimentioning
confidence: 99%
“…[1][2][3] Ongoing researches are trying to elucidate the mechanisms potentially responsible for inducing the immune response against SARS-Cov-2, including the role of HLA alleles in the affected individuals. 4 The HLA complex constitutes a specific group of molecules expressed on the cell surface, crucial for the recognition of nonself molecules by the acquired immune system. Their essential function is to bind and display antigens derived from pathogens on the cell surface and present them to the appropriate T lymphocytes, triggering an immune response.…”
mentioning
confidence: 99%
See 1 more Smart Citation